Pemberdayaan Masyarakat Melalui Pemeliharaan dan Perkandangan Ayam Kampung Unggul Balitnak (KUB) di Desa Pakatto Caddi Kabupaten Gowa Provinsi Sulawesi Selatan - Subhan Effendi; Nevyani Asikin; Ilham Ahmad (Jurnal Kemitraan Masyarakat, 2024)
The community's need for animal protein from poultry can be pursued through poultry farming businesses such as raising Balitnak Superior Village chickens (KUB). KUB chicken rearing has a great opportunity to be developed by livestock groups in Pakatto Caddi Village in order to reduce dependence on poultry that is encouraged to grow quickly. The KUB chicken rearing and housing extension program in Pakatto Caddi Village is one of the solutions for livestock business development in terms of overcoming food insecurity, reducing dependence on poultry commodities and building community independence in providing quality protein source food.